Hemorrhagic ascites in endometriosis: a case series and clinical implications - Elham Askary; Nahideh Afshar Zakariya; Zahra Parsaiyan; Saeed Alborzi; Tahereh Poordast (BMC Women's Health)
Abstract Background Hemorrhagic ascites is a rare clinical manifestation of endometriosis, often misdiagnosed due to its resemblance to malignancy. This study aims to highlight diagnostic and management challenges by presenting three cases. Case presentation Three nulliparous women presented with abdominal distension, pelvic pain, and large-volume bloody ascites. One had concurrent right-sided hemorrhagic pleural effusions. Imaging studies showed deep infiltrating endometriosis (DIE) without ovarian endometriomas in two patients. Laparoscopic surgery confirmed extensive endometriosis with 2–4 L of bloody ascitic fluid. Histopathological examination excluded malignancy and confirmed endometriosis. Postoperative medical therapy included hormonal suppression. Conclusion Bloody ascites is an uncommon but important presentation of severe endometriosis. These cases highlight the importance of considering endometriosis in the differential diagnosis of bloody ascites, particularly in reproductive-aged women. Surgical diagnosis and histopathologic confirmation are essential to rule out malignancy. A multidisciplinary approach and individualized fertility planning are crucial in managing these complex cases.